Experimetrics : econometrics for experimental economics / Peter G. Moffatt. - Moffatt, Peter G. (Palgrave, 2016)
An essential guide to techniques used to analyse experimental data in economics, written by one of the world's experts in the field. It is designed to show advanced economics students and researchers how to tackle difficult econometric problems inherent in the methodology such as between-subject heterogeneity, and upper and lower censoring.